Penerapan Kompilasi Hukum Islam Pasal 53 Dalam Pelaksanaan Pencatatan Pernikahan oleh PPN pada Kantor Urusan Agama (KUA) di Kecamatan Tanjung Pura - Abdullah Sani Kurniadinata; Satria Wiguna (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2020)
The purpose of this study was to find out the sound and explanation of the Compilation of Article 53, to know the clear law regarding pregnant marriage due to adultery which is regulated by law and Syara' and to know the procedures for registration of marriage and the marriage process carried out by pregnant women due to adultery. recorded by the Tanjung Pura District Religious Affairs Office. This type of research is a qualitative research with a field research approach (field research). Methods of collecting data by means of observation, interviews and documentation. The conclusion of this study that it has been carried out related to the application of the compilation of Islamic law article 53 in the implementation of marriage registration by VAT at the Office of Religious Affairs (KUA) of Tanjung Pura District is allowed and carried out as usual marriages without different procedures, with considerations: 1. Can save nasab for the baby, 2. Protecting the honor of women and families 3. Guaranteed survival for the baby in the womb and 4. Cessation of adultery previously committed. Keywords: Compilation of Islamic Law, Article 53 Marriage, PPN KUA